2021
DOI: 10.1039/d1ra03647e
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of ion-imprinted Fe3O4/carboxymethyl cellulose magnetic biosorbent: removal and recovery properties for trivalent La ions

Abstract: An Fe3O4/carboxymethyl cellulose magnetic biosorbent was prepared by ion-imprinting technology, showing good adsorption and selectivity properties for La(iii) with a high recovery efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 33 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…For example, Yang and co-workers prepared novel millimeter-scale hollow CMC-Al/PEI microspheres by using polyethylenimine (PEI) and glutaraldehyde (GA)-modified CMC-Al, which shows good adsorption performance to methyl blue. In our previous study, we found that CMC is a good biopolymer adsorbent for ITT and the prepared CMC/Fe 3 O 4 shows good adsorption performance to La 3+ . However, CMC is a water-soluble material, and it would result in a wastage problem during application in water, which would make CMC less efficient during the recycle and reuse process as an adsorbent.…”
Section: Introductionmentioning
confidence: 93%
“…For example, Yang and co-workers prepared novel millimeter-scale hollow CMC-Al/PEI microspheres by using polyethylenimine (PEI) and glutaraldehyde (GA)-modified CMC-Al, which shows good adsorption performance to methyl blue. In our previous study, we found that CMC is a good biopolymer adsorbent for ITT and the prepared CMC/Fe 3 O 4 shows good adsorption performance to La 3+ . However, CMC is a water-soluble material, and it would result in a wastage problem during application in water, which would make CMC less efficient during the recycle and reuse process as an adsorbent.…”
Section: Introductionmentioning
confidence: 93%
“…The magnetic biosorbent Fe 3 O 4 /CMC was successfully prepared by Liu et al using ion imprinting technology, with La 3+ serving as the template ion. 77 Velempini et al also used sodium carboxymethyl cellulose as the base for ion-imprinting for hexavalent chromium adsorption in an aqueous solution. 78 Monier et al reported using salicylaldehyde-carboxymethyl cellulose as a selective UO 2 2+ adsorbent.…”
Section: General Features Of Iipmentioning
confidence: 99%